Design and Simulation of Lightweight Identity Authentication Mechanism in Body Area Network. (19th April 2021) - Yang, Jianglong; Yang, Wanlin; Liu, Huwei; Zhou, Li
Abstract : Wearable medical devices rely on the human body to form a small LAN around the human body, called body area network (BAN). Users can use these devices to monitor the changes of various body indicators in real time. The physiological data involved in this process belongs to personal privacy. Therefore, the security requirements of BAN are relatively high, and its current research focus is on authentication mechanisms. To meet the requirements of security and resource consumption of BAN, this paper proposes a lightweight identity authentication mechanism that meets the characteristics of BAN resource constraints. Based on the characteristics of BAN, a simple and mature star topology structure is applied to establish the network model of BAN. For the human body in normal situations and emergencies, the corresponding authentication mechanism and encryption and decryption method of physiological data are designed by using the physical unclonable function (PUF) and cloud database, physiological data, and cross-correlation algorithm. Furthermore, the formal and informal security analysis of the designed authentication mechanism proves that the authentication mechanism designed in this paper has certain security, and the lightweight authentication mechanism is simulated and evaluated. The experimental results show that compared with the benchmarking mechanism, the authentication mechanism designed in this paper solves more security problems and has certain advantages in terms of calculation cost, communication cost, and energy cost.